SHE’RIY TARJIMADA RADIFNI AKS ETTIRISH MUAMMOLARI - Sapayeva, F.D. (SCIENCE and SOCIETY, 2023)
This article focuses on the study of genre problems of poetic translation, in particular, on the reflection of radif in translation. It is not surprising that the content of this problem on the example of Makhtumkuli’s poetry is embedded in the lines, although there is little poetic translation in practice, the use and recognition of these methods and techniques serves as a special foundation for translators.